KEMAMPUAN MENULIS KARANGAN EKSPOSISI DENGAN MENGGUNAKAN MEDIA BAGAN ARUS SISWA KELAS XI SMK NEGERI 4 PADANG TAHUN PELAJARAN 2012/2013 - Hermanto, Benny; Bahardur, Iswadi; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by the eight reasons. First, the teaching of writing just described in terms of the theories and practice are less than the maximum. Second, the book learning support is still lacking. Third, only use the lecture method of teaching. Fourth, students are difficult to distinguish and determine the type of essay exposition. Fifth, students are less able to use the Indonesian language is good and true. Sixth, students are less able to express an idea, notion, thought to be written in essay form. Seventh, the study did not use the Indonesian media. Eighth, the number of Indonesian hours only 2 sessions so as to practice writing essays exposition is not maximal. This study aims to describe the exposition essay writing skills by using media flow chart. This type of research is descriptive quantitative method. Population studies class XI student of SMK state 4 Padang, amounting to 294 people. Sample was 31 people. The sampling technique is random sampling. Instruments used performance tests essay writing exposition.Based on the analysis of research data. Perfect qualifications for indicators explain a subject matter in accordance with the object (chart). Qualification for the indicator does not affect the reader. More than enough qualifications to elaborate indicators objects clearly. Excellent qualification for the indicator using the facts. Average exposition essay writing skills of students by using media flow charts good qualification is 85% in the range 76-85%.